N-hexane neuropathy with vertigo and cold allodynia in a silk screen printer: A case study - Sunil Pradhan; Ruchika Tandon (International Journal of Occupational Medicine and Environmental Health, 2015)
N-hexane neuropathy is an occupational disease caused by exposure to n-hexane, which is used as a solvent in silk screen printing. Here, we describe a 35-year-old man, a silk screen printer by profession, who presented with dizziness, distal swelling of both lower limbs for 10 months and tingling and burning sensation in both feet for 9.5 months along with cold allodynia. The patient had normal results of a motor and sensory system examination, apart from an impaired temperature sense. Nerve conduction tests showed a conduction block in bilateral common peroneal nerves and absence of conduction in bilateral sural nerves. These symptoms resolved when further exposure to n-hexane was ceased but cold allodynia remained. Thus, cold allodynia and impaired temperature sense can be a manifestation of n-hexane neuropathy. Hence, abnormalities on nerve conduction studies can be detected in n-hexane neuropathy patients, even before clinical examination detects any such abnormalities. In the case of the patients presenting with sensory motor neuropathy, history of occupational exposure to n-hexane becomes important, as the sooner the disease is detected, the better the chances of recovery.